Determination of direct wave parameters for transmission of electromagnetic energy in a prismatic resonator with wool - Аврунин, О.Г.; Семенец, В.В.; Косулина, Н.Г.; Попрядухин, В.С.; Кускова, С.В. (Radiotekhnika, 2019)
The article is devoted to solving the theoretical problem of determining the parameters of a rectangular waveguide for efficient transfer of mm range electromagnetic energy to the prismatic resonator with the following parameters: width 800 mm; height 600 mm; length 300 mm. The length of the stimulating wave is λ = 8,333 mm (f = 36 GHz). As a result of theoretical studies, it has been found that the equality of transverse dimensions of the resonator and the feeding waveguide is required to obtain the maximum size of the stimulation (η) of electromagnetic oscillations in a prismatic resonator.